Perbandingan Peta Kendali Poisson Double Progressive Mean dan Peta Kendali u pada Produksi Roti di Pakbatteang Mandiri - Ningsi, Parida Ayu; Sirajang, Nasrah (ESTIMASI: Journal of Statistics and Its Application, 2026)
Pakbatteang Mandiri is a company that operates in the food industry by producing bread, but the bread production process shows that there are defects in the product so a control chart is needed to monitor the number of production defects. Control charts that are suitable for use for calculated data such as the number of production defects are control charts based on the Poisson distribution such as the u control chart and the Poisson Double Progressive Mean control chart. This research aims to obtain a comparison of the Poisson Double Progressive Mean control chart and the u control chart for bread production in Pakbatteang Mandiri. The results of this research show that the Poisson Double Progressive Mean control chart detects more observation points that are out of control when compared to the u control chart. Based on the relatively small ARL value, the performance of the Poisson Double Progressive Mean control chart is more sensitive in detecting out of control than the u control chart.